Sexual harassment and its relationship to unease at work - Bengasmia, Hadjer; Khelassi, Mourad (Journal of Human Sciences, 2023)
This study aimed to reveal the phenomenon of sexual harassment behavior in working women and its relationship to their discomfort in the workplace, in addition to identifying the types of sexual harassment behaviors in Algerian institutions. And the Milk Production Corporation, the researchers relied on the descriptive approach using the content analysis method, and the interview was used as a tool for collecting information. In her workplace, which leads to the creation of a state of tension and imbalance, which generates a feeling of insecurity and makes her suffer suffering in her position.